2010
DOI: 10.4314/wajm.v29i1.55947
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sociodemographic and Drug Abuse Variables in Patients with Alcohol and Drug Use Disorders in a Nigerian Treatment Facility

Abstract: BACKGROUND: Globally, patterns of the use of psychoactive substances have been changing. OBJECTIVE: To evaluate the trend in two five-year periods,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 5 publications
6
25
0
Order By: Relevance
“…The predominance of cannabis (55%) over other drugs in this study is in keeping with the report by Adamson et al (2010) of a change in the pattern of drugs used by patients admitted to the DATER unit between 2002 and 2007 compared with between 1992 and 1997. They reported that the rate of cannabis use by admitted patients increased from 26.6% to 53.3%, while the use of cocaine and opiates decreased from 44.0% and 22.0% to 17.1% and 8.6% respectively.…”
Section: Discussionsupporting
confidence: 78%
“…The predominance of cannabis (55%) over other drugs in this study is in keeping with the report by Adamson et al (2010) of a change in the pattern of drugs used by patients admitted to the DATER unit between 2002 and 2007 compared with between 1992 and 1997. They reported that the rate of cannabis use by admitted patients increased from 26.6% to 53.3%, while the use of cocaine and opiates decreased from 44.0% and 22.0% to 17.1% and 8.6% respectively.…”
Section: Discussionsupporting
confidence: 78%
“…The scheme [15] is a social security system which seeks to guarantee the provision of needed health services to persons on the payment of token contributions at regular intervals. However it makes provision for admission in a ward for only 15 days in a year and, for now, has well established program for only the formal sector, consisting of the public service and organized private sector; whereas two-third to three-quarter of those accessing substance abuse treatment in Nigeria are unemployed [16] and are thereby effectively barred from the funding opportunities afforded by the health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical setting would naturally be expected to be a conducive environment for long term substitution/maintenance therapy. On the contrary, none of the units embraced the therapy, despite the demand for treatment by persons who abused opiates [16]. Two possible reasons for this are, one, methadone and other substitution/maintenance medications are yet to be approved by the National Agency for Food and Drug Administration and Control; and two, at present, there is no existing framework for their use in the country.…”
Section: Discussionmentioning
confidence: 99%
“…The unit has been described elsewhere [14][15][16]. It was established in 1983 within the premises of its 526-bed parent hospital, the Neuropsychiatric Hospital, Aro, Abeokuta, which is one of the 8 federal neuropsychiatric hospitals in Nigeria.…”
Section: Methodsmentioning
confidence: 99%